Restructuring Examination System of Institute of Engineering for Establishing Center of Excellence in Engineering Education - Bajracharya, Tri Ratna; Dawadi, Babu Ram; Sapkota, Ram Chandra (Journal of the Institute of Engineering, 2018)
There exists different parameters that act as influencing factors to measure the quality of technical education. Nature of examination with its process and activities has direct and indirect relationship towards quality product and result status in any academic institution. Institute of Engineering (IOE) is continuously enhancing the examination process with the objective to increase the quality and pass rate in the semester examination. Being to conduct several bi-annual exams, Examination Control Division (ECD) of Institute of Engineering (IOE) is mostly the busy organization that has to manage examinations for bachelor, masters and PhD degree programs throughout the year. ECD conducts by-annual semester exams for regular and back exam of bachelor of engineering students having 10 streams (Civil, Computer, Electronics, Electrical, Mechanical, Geomatics, Agriculture, Industrial, Architecture and Automobile) in its four constituent campuses and ten affiliated colleges. Similarly, ECD also conducts bi-annual exams for masters of engineering programs having seven streams and 24 sub-streams. There are more than 16,000 examinees in the bachelor exam including regular and back. Additionally, successful conduction of BE/BArch/ M.Sc. entrance examinations is also an integral duty of ECD. The student pass rate in the semester exams of IOE is below expectations. This study is mostly focused on finding the factors affecting the quality results and approaches of optimizations for better education at IOE. After reviewing several factors, we proposed “restructuring of regular and back paper examinations" as one of the major approach that will help to increase the quality of education and consequently increase the pass rate in the semester examination system of IOE. Journal of the Institute of Engineering, 2018, 14(1): 75-81